Use S-FUNCTION BUILDER in MATLAB/SIMULINK - V. G. Mikhailov (Системный анализ и прикладная информатика)
The analysis of used methods of the task of external indignation in MATLAB/SIMULINK by means of the generator of white noise and the subsequent filtration and the task on points in MS.Excel (1000 values) is carried out. It is established that they do not provide the decision of the problems demanding great volumes of the data and necessary speed and cannot will be applied to more challenges (modelling of movement and loading the vehicle, the task of trajectories of flight, the equipment of passage of breeds and others). Existing approaches and receptions can be used only for the decision of simple problems. It is noticed that the majority of researchers do not use the module S-FUNCTION BUILDER because of misunderstanding of its adjustment and mastery of a language C/C++. Problems with compilation of programs in the module S-FUNCTION BUILDER are revealed. Decisions of their elimination offered at forums are not convenient in practice. The decision of this problem through installation of system variable Windows is offered.The approach and reception of the task of external indignation by means of the module S-FUNCTION BUILDER is offered, allowing to solve these problems.Adjustment and module use S-FUNCTION BUILDER for formation of external indignation for these problems are in detail considered.The program of realization of the task of external indignation in language C/C++ is offered, the initial text of the program is resulted.The block diagram of use of the module S-FUNCTION for the decision of joint modelling of movement and loading the vehicle is shown.Scopes of the offered program and the approach for probes mechatronic systems are considered.The offered approach and reception of the task of external indignation by means of the module S-FUNCTION BUILDER allows to solve challenges and to pass to more difficult imitating modelling with participation of the person.